(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Neostigmine is a drug commonly used, thus making it a possible second line of treatment after conservative methods have failed and surgery is not feasible. Case presentation: A para 3+1 gravida 4 was admitted for elective caesarean delivery because of two previous scars at term. She had undergone five previous abdominal surgical procdures. Her antenatal follow-up was uneventful. Perioperative vital signs were within normal limits, with normal systemic examination findings. She had abdominal surgical scars, three of which were well healed with no hernia orifices. Leopold’s maneuvers and perioperative laboratory parameters were within normal limits. Intraoperatively, dense adhesions involving the omentum and small gut were attached to the anterior abdominal and uterine walls along the incision site. The washout of the abdomen and close inspection of the omentum confirmed no gut or bladder injury. Postoperatively, she had progressive abdominal distension with constipation on day three. Abdominal X-ray and computed tomography revealed multiple air-fluid levels and grossly dilated bowel loops. There was no improvement after conservative management, and on the sixth postoperative day, the decision to use neostigmine in an intensive care unit setting was reached. Following a single attempt, success was achieved, and the patient opened her bowels. Subsequently, she regained normal bowel function, and after two months of follow-up, the patient is faring well. Discussion: Ogilvie’s syndrome is defined as colon pseudoobstruction. It is rare (1:1000 admissions annually) but causes severe morbidity and mortality. The rate is noted to be increasing because of increased cesarean delivery rates globally. Diagnosis is based on clinical and imaging findings. Challenges in diagnosis due to challenges in identification and reduced clinician index of suspicion lead to delays in treatment. Neostigmine plays a role in medical management, whereas conservative management has not been effective.